HUBUNGAN ANTARA SELF CONTROL DENGAN QUALITY OF LIFE PADA MANTAN PENGGUNA NAPZA DI SUMATERA BARAT - Bela Sari Duri; Rida Yanna Primanita (Universitas Negeri Padang, 2022)
Abstract: The relationship between self control with quality of life on ex-drug users in West Sumatera. This exploration is a correlational quantitative examination which is one type of examination to decide the connection between factors. This review means to look at the connection between restraint and personal satisfaction in previous medication clients in West Sumatra. Scientists utilized snowball inspecting as an examining procedure, where the quantity of tests was 52 individuals. The information assortment strategy utilizes a discretion scale and a personal satisfaction scale. The information is handled by utilizing the item second connection investigation method. The outcomes show that there is a connection between poise and personal satisfaction in previous medication clients in West Sumatra where the relationship esteem (r) is .562 with p = .000 (p < .05). Abstrak: Hubungan self control dengan quality of life pada mantan pengguna napza di Sumatera Barat. Penelitian ini merupakan penelitian kuantitatif korelasional yang merupakan salah satu bentuk penelitian untuk mengetahui hubungan antar variabel. Penelitian ini bertujuan untuk melihat hubungan antara self control dengan quality of life pada mantan pengguna napza di Sumatera Barat. Peneliti menggunakan snowball sampling sebagai teknik pengambilan sampel, yang mana jumlah sampel sebanyak 52 orang. Teknik pengambilan data menggunakan skala self control dan skala quality of life. Data diolah dengan menggunakan teknik analisis korelasi product moment. Hasil penelitian menunjukkan bahwa terdapat hubungan antara self control dengan quality of life pada mantan pengguna napza di Sumatera Barat dimana nilai korelasi (r) sebesar .562 dengan nilai p = .000 (p < .05).